Tourism and Creative Economy Entrepreneurs’ Resilience in The Covid-19 Pandemic in West Java - Putra, Rifki Rahmanda; Sujawoto, Fitra Ananta (Jurnal Penelitian Pariwisata, 2023)
This study aims to determine the impact of the Covid-19 pandemic on the economic conditions of tourism and creative economy entrepreneurs and to identify their efforts to survive the impact of the Covid-19 pandemic in West Java. The quantitative approach with a survey method was used by presenting data through a survey of 200 tourism and creative economy entrepreneurs in West Java and simultaneously conducting open interviews to dig deeper information from the structured questions on the survey instrument. The data analysis technique used is quantitative descriptive analysis. The results show that the pandemic has impacted tourism and creative economy entrepreneurs economically, from a decrease in income to a loss of income. Efforts to survive include innovating in their businesses, using their savings, and looking for new jobs outside the tourism and creative economy sectors. In addition, collaboration and assistance are needed in business safety nets, knowledge-sharing forums in online training, and developing operating standards for tourism businesses and the creative economy that adapts to pandemic conditions. Keywords: Creative Economy Entrepreneurs, Covid-19 Pandemic, Tourism Resilience, West Java Tourism